Statistical atlases and computational models of the heart. Imaging and modelling challenges : Second international workshop, STACOM 2011, Held in conjunction with MICCAI 2011, Toronto, ON, Canada, September 22, 2011, Revised Selected Papers - Camara, Oscar (Lecture Notes in Computer Science, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the Second International Workshop on Statistical Atlases and Computational Models of the Heart: Imaging and Modelling Challegenges, STACOM 2011, held in conjunction with MICCAI 2011, in Toronto, Canada, in September 2011. The 28 revised full papers were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on EP simulation challenge, motion tracking challenge, segmentation challenge, and regular papers.